2013
DOI: 10.1038/ncomms3234
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Bag6 and the TRC pathway in proteasome assembly

Abstract: The 26S proteasome has an elaborate structure, consisting of 33 different subunits that form the 20S core particle capped by the 19S regulatory particle on either end. Several chaperones that are dedicated to the accurate assembly of this protease complex have been identified, but the mechanisms underlying proteasome biogenesis remain unexplored so far. Here we report that core particle assembly becomes less efficient if the TRC pathway, which mediates insertion of tail-anchored proteins, is defective. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…Induction of PRB1 may reflect compensatory upregulation of vacuolar protein degradation, which may be necessary for the disposal of aberrant proteins and for maintenance of the amino acid pool required for cell survival under proteasome impairment [37]. In addition, we found that GET3, which participates in CP assembly [32], also contained PACE core in the promoter and was induced by Rpn4. This observation supports the importance of PACE core for proteasome assembly.…”
Section: -(A/ G/t)g(t/g)ggc(a/g)-3mentioning
confidence: 77%
“…Induction of PRB1 may reflect compensatory upregulation of vacuolar protein degradation, which may be necessary for the disposal of aberrant proteins and for maintenance of the amino acid pool required for cell survival under proteasome impairment [37]. In addition, we found that GET3, which participates in CP assembly [32], also contained PACE core in the promoter and was induced by Rpn4. This observation supports the importance of PACE core for proteasome assembly.…”
Section: -(A/ G/t)g(t/g)ggc(a/g)-3mentioning
confidence: 77%
“…It is expected that the mammalian homologs, along with Bag6, play a similar role (23)(24)(25)(26)(27). Bag6 also interacts with other proteins such as apoptosisinducing factor, glycoprotein 78 (gp78), regulatory particle 5, and brother of regulator of imprinted sites (BORIS) (16,(27)(28)(29)(30)(31)(32) and can homo-oligomerize, increasing the level of complexity (30). These findings build a picture of Bag6 as a central hub for a diverse physiological network of proteins.…”
mentioning
confidence: 95%
“…Specifically, β subunits were poorly incorporated and this correlated with poor recruitment of CP assembly intermediates to the ER membrane. Strong genetic interactions between proteasome assembly factors and yeast components of the tail-anchoring pathway were also observed, suggesting a conserved mechanism involving CP assembly at ER membranes might be at play (Akahane et al 2013). The same study also reported that Bag6 was required for the stability of the Nas2 module as Bag6 knockdowns resulted in accumulation of RP-like species lacking Rpt4 and Rpt5 (Akahane et al 2013), suggesting Bag6 might have multiple roles in proteasome assembly.…”
Section: Localization In Assemblymentioning
confidence: 82%
“…Moreover, CP assembly defects were observed when TRC40 or Bag6, two proteins involved in the pathway which inserts tail-anchored proteins into the mammalian ER membrane, were knocked down (Akahane et al 2013). Specifically, β subunits were poorly incorporated and this correlated with poor recruitment of CP assembly intermediates to the ER membrane.…”
Section: Localization In Assemblymentioning
confidence: 99%